Cutaneous Aspergilosis Caused by Aspergillus Flavus: A Case Report - Sheilaadji, Maria Ulfa; Agusni, Indropo; Astari, Linda; Anggraeni, Sylvia; Widia, Yuri; Ervianti, Evy (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2021)
Background: Cutaneous aspergillosis occurs relatively less frequent and therefore remains poorly characterized. Cutaneous aspergillosis can be as primary or secondary infection. Primary cutaneous aspergillosis usually involves sites of skin injury, intravenous catheter, traumatic inoculation, and associated with occlusive dressings. Secondary lesions result from contiguous extension from infected underlying structures or from widespread blood-borne seeding of the skin. Purpose: To know the skin manifestation, efflorence, examination and therapy of cutaneous aspergillosis. Case: A man complaint itchy redness macule and pimples on the right arm since 2 weeks. Initially just felt a little then expands. Patients with post operative brachial injury and uses a cast during one month. On examination there are erythematous macule unsharply marginated with papules. Potassium hydroxide examination, shows conidiophores, dichotomously branching and septate hyphae appropriate description with Aspergillosis Sp. Cultures found grow granular colonies, flat often with radial grooves, yellow at first but quickly becoming bright to dark yellow-green with age, For the identification microscope from the culture specimen there was conidia, phialde, conidiophore and vesicle that suitable with Aspergillus flavus. Patients received itraconazole 2 x 200 mg for 6 weeks and obtained satisfactory results. Discussion: Healthy hosts can develop cutaneous aspergillosis in surgical wounds, by traumatic inoculation, at sites associated with occlusive dressings. In some instances, a presumptive diagnosis of primary cutaneous aspergillosis can be made immediately by examining a potassium hydroxide preparation and culture. Conclusion: Diagnose of cutaneous aspergillosis can establish by potassium hydroxide and culture examination, therapy with itraconazole 2x 200mg give satisfactory results.